2010
DOI: 10.1186/1477-3155-8-34
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial activity of spherical silver nanoparticles prepared using a biocompatible macromolecular capping agent: evidence for induction of a greatly prolonged bacterial lag phase

Abstract: BackgroundWe have evaluated the antimicrobial properties of Ag-based nanoparticles (Nps) using two solid phase bioassays and found that 10-20 μL of 0.3-3 μM keratin-stabilized Nps (depending on the starting bacterial concentration = CI) completely inhibited the growth of an equivalent volume of ca. 103 to 104 colony forming units per mL (CFU mL-1) Staphylococcus aureus, Salmonella Typhimurium, or Escherichia coli O157:H7 on solid surfaces. Even after one week at 37°C on solid media, no growth was observed. At … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 36 publications
(46 reference statements)
2
15
0
Order By: Relevance
“…Few studies cover the growth patterns of food-borne pathogenic bacteria like L. monocytogenes or S. enterica when exposed to silver ions over time, these being most commonly done with silver nanoparticles and on E. coli or S. aureus. In a study with silver nanoparticles against Salmonella typhimurium, Irwin et al found the increase in the lag phase with increasing silver nanoparticle concentration to be linear, all samples finally reaching maximum growth (Irwin et al, 2010). In other reports, a delay in proliferation or increase in the lag phase can also be noted which varies from 2-4 h (Sondi and Salopek-Sondi, 2004) to 24 h (Pal et al, 2007).…”
Section: Viability Vs Cultivabilitymentioning
confidence: 92%
“…Few studies cover the growth patterns of food-borne pathogenic bacteria like L. monocytogenes or S. enterica when exposed to silver ions over time, these being most commonly done with silver nanoparticles and on E. coli or S. aureus. In a study with silver nanoparticles against Salmonella typhimurium, Irwin et al found the increase in the lag phase with increasing silver nanoparticle concentration to be linear, all samples finally reaching maximum growth (Irwin et al, 2010). In other reports, a delay in proliferation or increase in the lag phase can also be noted which varies from 2-4 h (Sondi and Salopek-Sondi, 2004) to 24 h (Pal et al, 2007).…”
Section: Viability Vs Cultivabilitymentioning
confidence: 92%
“…Due to these antimicrobial properties, their incorporation into medical devices, tissues and other health related products promote higher preventive infection control [3,4]. …”
Section: Introductionmentioning
confidence: 99%
“…Even after one week at 37°C on solid media, no growth was observed. At lower Np concentrations, visible colonies were observed, but they eventually ceased growing [13].…”
Section: Bodymentioning
confidence: 99%